THE IMPACT OF GENERATIVE ARTIFICIAL INTELLIGENCE ON EFL STUDENTS’ PRONUNCIATION, ANXIETY, MOTIVATION, AND SOCIAL INTERACTION - Nopelisa Pelawi; Christina Natali Saragi (Universitas HKBP Nommensen, 2026)
This study investigates the impact of Generative Artificial Intelligence (GenAI) on students’ pronunciation ability, speaking anxiety, speaking motivation, and social interaction in English as a Foreign Language (EFL) learning. Although artificial intelligence technologies are increasingly integrated into language classrooms, empirical evidence regarding their combined effects on cognitive and affective dimensions of speaking development remains limited, particularly in Indonesian secondary school contexts. This research employed a quantitative experimental design involving 60 Grade X students at SMA Negeri 1 Tigapanah. The participants were divided into an experimental group and a control group. The experimental group received GenAI-assisted speaking instruction, while the control group was taught using conventional classroom methods. Data were collected through pronunciation tests and Likert-scale questionnaires measuring speaking anxiety, motivation, and social interaction. The results show that the experimental group demonstrated greater improvement in pronunciation ability (pre-test M = 67.0; post-test M = 79.0) compared with the control group (pre-test M = 67.5; post-test M = 72.0). Statistical analysis using paired-sample t-tests confirmed a significant improvement in pronunciation for the experimental group (p < 0.05). In addition, GenAI-assisted learning reduced students’ speaking anxiety and increased their motivation to participate in speaking activities. However, the findings also indicate a slight decline in peer interaction, as some students preferred practicing with AI rather than engaging in direct communication with classmates. From the perspective of Cultural Historical Activity Theory (CHAT), GenAI functions as a mediating tool that reshapes the classroom activity system by influencing cognitive, emotional, and social dimensions of learning. These findings suggest that while GenAI effectively supports pronunciation development and affective engagement, its integration should be carefully balanced to maintain meaningful social interaction in EFL classrooms.